The contradictory college : the conflicting origins, impacts, and futures of the community college - Dougherty, Kevin James (SUNY series, frontiers in education., 1994)
Annotation This book systematically analyzes the evidence on four key issues that have divided commentators on the community college: The community college's impact on students, business, and the universities; the factors behind its rise since 1900; the cause of its swift vocationalization after 1960; and what direction the community college should take in the future.